2022
DOI: 10.1038/s41598-022-12839-5
|View full text |Cite
|
Sign up to set email alerts
|

Symptom burden correlates to impairment of diffusion capacity and exercise intolerance in long COVID patients

Abstract: After acute infection with the SARS-CoV-2 virus, a considerable number of patients remains symptomatic with pathological changes in various organ systems. This study aimed to relate the physical and mental burden of symptoms of long COVID patients to the findings of a somatic evaluation. In patients with persistent long COVID symptoms three months after acute infection we assessed physical and mental health status using the SF-36 questionnaire. The cohort was dichotomised by the results (upper two quartiles vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Using 6MWT in PCS, a recent study showed that patients with lower DLCO had a worse performance during the test, including a higher frequency of desaturation during exercise ( van den Borst et al, 2021 ). Another study showed a correlation of well-being to functional values of DLCO and the 6MWT in patients with PCS ( Kersten et al, 2022 ). Using linear regression for the 6MWT distance as a dependent variable, Townsend et al (2021) observed that the reduced covered distance was associated with the length of hospital stay in patients with PCS, but no other features; however, these authors did not assess the impact of lung function on functional exercise capacity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Using 6MWT in PCS, a recent study showed that patients with lower DLCO had a worse performance during the test, including a higher frequency of desaturation during exercise ( van den Borst et al, 2021 ). Another study showed a correlation of well-being to functional values of DLCO and the 6MWT in patients with PCS ( Kersten et al, 2022 ). Using linear regression for the 6MWT distance as a dependent variable, Townsend et al (2021) observed that the reduced covered distance was associated with the length of hospital stay in patients with PCS, but no other features; however, these authors did not assess the impact of lung function on functional exercise capacity.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in conformity with a systematic review on the pulmonary function in patients with PCS that showed a prevalence of 39% and 15% for DLCO abnormality and restrictive pattern, respectively ( Torres-Castro et al, 2021 ). It is worth noting that in our multiple regression model, the drop in DLCO (a marker of pulmonary vascular damage) and, to a lesser extent, the drop in FVC (a marker of impaired lung mechanics) resulted in a longer TGlittre time ( Kersten et al, 2022 ; Lopes, 2019 ). Using 6MWT in PCS, a recent study showed that patients with lower DLCO had a worse performance during the test, including a higher frequency of desaturation during exercise ( van den Borst et al, 2021 ).…”
Section: Discussionmentioning
confidence: 91%
“…Conversely, our cohort consisted mostly of mild-to-moderate initial COVID-19 cases and generally showed normal workload and VO 2 values. Post-COVID-19 patients with prior hospitalization due to COVID-19 have been shown to have more pathological findings [ 21 ]. Previously hospitalized patients also had worse peak VO 2 values in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that even 6 months after hospitalization for COVID-19 disease, as many as 68% of affected individuals still suffer from at least one symptom, such as fatigue or dyspnea, and 49% continue to do so even after 12 months [ 5 ]. Reduced performance on the 6 min walking distance test (6-MWT) as well as impaired pulmonary diffusion capacity 3 months after COVID-19 disease has been reported [ 6 ]. Although several studies have observed cardiopulmonary damage secondary to COVID-19 disease [ 7 , 8 ], neither cardiac magnetic resonance imaging (MRI) nor pulmonary function or cardiopulmonary exercise testing revealed pathologies explaining persistent symptom burden [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%